8-3x=4x-12+6
-7x=-14
x=2
2006-11-06 13:02:51
·
answer #1
·
answered by coolchess123 3
·
1⤊
1⤋
Distribute the 4 through the parentheses:
8 - 3x = 4x - 12 + 6
Combine the -12 and +6:
8 - 3x = 4x - 6
Now add 3x (to cancel -3x) to both sides:
8 = 7x - 6
And add 6 (to cancel -6) to both sides:
14 = 7x
Now divide both sides by 7:
2 = x
Therefore x = 2.
I suspect you are doing the following:
8 - 3x = 4x *plus* 12 + 6 <-- mistake
8 - 3x = 4x + 18
-3x = 4x + 10
Then if you make another mistake with the signs you might get:
4x - 3x = 10 <-- another mistake
x = 10
The correct answer is:
x = 2 as shown above.
You can double-check this by putting it in the equation:
8 - 3(2) = 4(2 - 3) + 6
8 - 6 = 4(-1) + 6
2 = -4 + 6
2 = 2 <-- check
So x = 2
2006-11-06 13:06:26
·
answer #2
·
answered by Puzzling 7
·
0⤊
0⤋
8- 3x= 4(x -3) =6 distribute the 4
4x-12 the equation then becomes this
8-3x=4x-12+6
-4x -4x now isolate the x's on left side
8-7x= (-12) +6 further isolate the x by moving
-8 -8 the 8 from left side to right
-7x= -20+6 so the equation becomes, subtract on the right you get:
-7x = -14 now divide by -7 (when dividing by 2 negatives and you get a positive)
-7x = -14
___________
-7 - 7
therefore the answer is x= 2
2006-11-06 13:25:21
·
answer #3
·
answered by trish the dish 3
·
0⤊
0⤋
x=2
2006-11-06 13:01:32
·
answer #4
·
answered by 7
·
1⤊
0⤋
ok lets see
8-3x=4(x-3)+6
8-3x=(4x-12)+6 remove the brackets
8-3x=4x-12+6
8-3x=4x-6 group the like terms
8+6=4x+3X
14=7x
14/7=x
2 =x
well. ther u go
i did it step by step for u
2006-11-06 13:07:40
·
answer #5
·
answered by dart 3
·
0⤊
0⤋
8 - 3x = 4(x - 3) + 6
becomes 2 = 4x - 12 + 3x
becomes 14 = 7x
Therefor 2 = x
2006-11-06 13:05:17
·
answer #6
·
answered by Dan S 7
·
0⤊
1⤋
8-3x=4(x-3)+6 first distribute 4(x-3) then youll get 8-3x=4x-12+6 then combine -12+6 then youll get 8-3x=4x-6 then add 6 to both sides and youll get 14-3x=4x then add your 3x to both sides giving you 14=7x then divide by 7 and youll get 2=x hope this helps
2006-11-06 13:09:55
·
answer #7
·
answered by gary_e_6990 2
·
0⤊
0⤋
8-3x=4(x-3)+6
8 - 3x = 4x - 12 + 6
8 - 3x = 4x - 6
-3x = 4x -6 -8
-3x = 4x - 14
-3x -4x = -14
-7x = -14
7x = 14 (The minus signs cancel each other out)
x = 14/7
x = 2
2006-11-07 00:10:19
·
answer #8
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
8-3x = 4(x-3) + 6
8-3x = 4x - 12 + 6
8-3x = 4x - 6
8 - 6 = 2(combine like terms)
-3x + 4x = x(combine like terms)
x = 2
2006-11-06 13:16:41
·
answer #9
·
answered by babyblue17 2
·
0⤊
0⤋
The first thing you do is distribute the 4 to the X and -3 in ().
Then you well add your like terms on the left side( -12 +6)
Then you will combine like terms
2006-11-06 13:05:26
·
answer #10
·
answered by Mesasabi 3
·
0⤊
0⤋
8 - 3x = 4x - 12 +6
8 - 3x = 4x - 6
-3x = 4x - 14
-7x = -14
x = 2
2006-11-06 13:14:12
·
answer #11
·
answered by wangs4 2
·
0⤊
0⤋